Engineering Dual Begomovirus-Bemisia tabaci Resistance in Plants. (January 2017) - Zaidi, Syed Shan-e-Ali; Briddon, Rob W.; Mansoor, Shahid
Abstract : The whitefly Bemisia tabaci is an important pest of many economically important crops and the vector of begomoviruses (family Geminiviridae ). Recently, the expression of insecticidal proteins and/or toxins or double-stranded (ds)RNA homologous to B. tabaci genes has been demonstrated to provide the plant with protection against B. tabaci and the viruses that it transmits.